The Relationship Between The Implementation of the Double Track Culinary Program and The Entrepreneurial Interest of High School Students in East Java - Damayanti, Safira; Nurlaela, Luthfiyah; Rizkiyah, Nurul Farikhatir; Ahmi, Hanif Naufal (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This research is against by the importance of the double track program initiated by the East Java Provincial Government as an effort to provide vocational skills for high school students, particularly in culinary arts, to provide them with competencies after graduation. The purpose of this research is to discuss the relationship between the implementation of the culinary double track program and students entrepreneurial interest in East Java. A quantitative method with a correlational design was practised. The study was conducted at four high schools implementing the double track program, involving 11th and 12th grade students enrolled in the culinary program. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. The research instrument consisted of two variables: the implementation of the culinary double track program (X) and entrepreneurial interest (Y). Data analysis was conducted using the Pearson Product Moment correlation test, yielding a correlation coefficient of 0.734 with a significance level of p < 0.001. The results indicate a positive and significant relationship between the implementation of the culinary double track program and students entrepreneurial interest.